Posted by
**manny** on
.

1.)correct

2.)wrong---> the first term is wrong

4(3a^2)^2 = 36a^4

3.) not sure on this one

4.) wrong---> - square root of six is not a solution

Hope this Helps!

1)find p(-3)if p(x)=4x^3-5x^2+7x-10

=-184

2)If r(x)=4x^2-3x+7,find r(3a^2)

=12a^4-9a^2+7

3)Write the expression 9n^6+7n^3-6 in quadratic form,if possible

=9(n^3)^2+7(n^3)-6

4)solve b^4+2b^2-24=0

=-2,2,-isquare root of 6

4)it has to be. my choices are;

A.-2,-square root of 6,square root of 6,2

B.-square root of 6,2,2i,i square root of 6

C.my previous answer

D.-2i,2i,- square root of 6,square root of 6

its weird but that's how it is in my book

i think one solution is

square root of 6i--->

or i square root of 6

but i don't think my answer appears in your solutions

______________________________

sorry im not that much of help!